Serum and urinary essential trace elements in association with major depressive disorders: a case–control study - Fu, Jiyong; Wang, Qinqin; Wang, Na; Li, Shilong; Zhang, Hongwei; Zhu, Yuxing; Guo, Hua; Wang, Fukun; He, Lei; Xia, Shuang; Cao, Bing (Frontiers in Psychiatry, 2023)
Introduction The etiology and pathophysiology of major depressive disorders (MDDs) remain unclear. Increasing evidence has demonstrated that essential trace elements (ETEs), such as iodine (I), zinc (Zn), copper (Cu), selenium (Se), cobalt (Co), and molybdenum (Mo), play vital roles in MDDs. Methods In total, 72 patients with MDD and 75 healthy controls (HCs) in the Zhumadian Second People's Hospital, Henan Province, China were recruited in our study. The levels of different ETEs were examined in both serum and urine, using an inductively coupled plasma mass spectrometer (ICP-MS), for both the MDD patients and HCs. Results The serum levels of I, Se, Cu, and Mo were significantly lower in the MDD patients compared to the HCs (p < 0.05), and the urinary levels of I and Zn were significantly higher in the MDD patients compared to the HCs (p < 0.05). The serum concentration of I (Q3: OR = 0.210, Q4: OR = 0.272) was negatively associated with MDD after adjusting for potential confounders, including age, gender, and BMI, and the urinary concentration of I (Q4: OR = 2.952) was positively associated. Conclusions The higher levels of I, Se, Cu, and Mo in serum might be protective against the development of MDD, and the excess I and Zn in urine may be associated with MDD pathogenesis. Future research needs to gain a deeper understanding of the metabolic pathways of ETEs, especially I, Se, Zn, Cu, and Mo, in MDD, and their role in the pathogenesis of depression.